Pengaruh Strategi Bauran Pemasaran terhadap Peningkatan Loyalitas Nasabah pada BPRS Bhakti Sumekar Kantor Cabang Pamekasan - Yenny Kuratul Aini; Wadhan Wadhan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
The Institute of Syariah banking continues to grow in Indonesia from urban to rural areas, particularly BPRS Bhakti Sumekar on branch office of  Pamekasan in the activities implementation  based on syariah principles, as well as in terms of marketing. BPRS Bhakti Sumekar on branch office of Pamekasan is one financial institution that has increased exponentially customers annually. The increase in the number of clients allegedly because of the trust and customer satisfaction so as to form loyalty. One of the advantages possessed by the BPRS Bhakti Sumekar on branch office of Pamekasan in terms of products, namely savings Barokah with the principle wadi'ah (surrogate) and sharia-based providing easiness for customers with initial deposit   and the minimum balance of Rp. 10.000 as well as free of administrative costs that are not owned by other Syariah financial institutions in Pamekasan. Based on this background, researchers interested in conducting research with the title " The Effect of Marketing Mix Strategy Towards Customer Loyalty Enhancement to BPRS Bhakti Sumekar on Branch Office of Pamekasan”. The purpose of this research to find out is there any influence of marketing mix strategy towards customer loyalty enhancement and what variables (product, price, place, promotion, people, physical evidence and process) the most dominant influence on customer loyalty enhancement. This type of research is a field research (field research) using a quantitative approach. The research population is all customers of BPRS Bhakti Sumekar on branch office of Pamekasan by using the nonprobability sampling and sampling insidential method and determination of the samples number with formula slovin the error rate of 5%.  The analysis technique is multiple linear regression analysis. The results of simultaneous calculations obtained Fcount amounted to 156.689> F table amounted to 3.86 which means accepting the hypothesis there is significant influence between marketing mix strategy (product, price, place, promotion, people, physical evidence and process) Towards the customer loyalty enhancement. While the partial test results obtained Tcount product, price, place, promotion, people, physical evidence and process respectively 3.306, 4.970, 3.180, 4.906, 3.977, 5.643, and 5.086 greater than Ttable amounted to 1,649, which means partially declared significant. So promotion (promosi) is the variable most dominant influence towards the customer loyalty enhancement in BPRS Bhakti Sumekar on Branch Office of Pamekasan.